2018
DOI: 10.1155/2018/2313021
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Research of the Active Ingredients from Traditional Chinese Medical Plant Polygonum Cuspidatum

Abstract: In recent years, the utilization of Chinese native medicine and other plant extracts in the treatment of diseases has attracted extensive attention, especially in the area of malignant tumors. However, lots of herbal remedies active ingredients have not been found or have been discovered but not effectively developed and applied. Therefore, screening new Chinese medicine active components and determining their antitumor effects have become a new breakthrough in the prevention and treatment of tumor disease. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 76 publications
1
16
0
1
Order By: Relevance
“…Resveratrol was originally extracted from the roots of Polygonum cuspidatum and is also found in red wine, grapes, and peanuts. 24 Moreover, resveratrol is the most studied monomer of Polygonum cuspidatum and is one of the major ingredients in Polygonum cuspidatum extract. 12 Pan et al reported that 7 ingredients were identified from the crude extract of Polygonum cuspidatum using the UPLC-MS/MS method, including resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol was originally extracted from the roots of Polygonum cuspidatum and is also found in red wine, grapes, and peanuts. 24 Moreover, resveratrol is the most studied monomer of Polygonum cuspidatum and is one of the major ingredients in Polygonum cuspidatum extract. 12 Pan et al reported that 7 ingredients were identified from the crude extract of Polygonum cuspidatum using the UPLC-MS/MS method, including resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Polygonum cuspidatum has documented anti-tumor, antimicrobial, anti-inflammatory, neuroprotective, and cardioprotective effects (73,74), with the polyphenol resveratrol being one of the main active constituents. Previous in vitro testing has documented that resveratrol exhibited activity against log phase spirochetes of Borrelia burgdorferi and Borrelia garinii, minimal activity against borrelia round bodies, and no significant activity against borrelia associated biofilms (63).…”
Section: Discussionmentioning
confidence: 99%
“…Polygonum cuspidatum is commonly used by Lyme disease patients manage their symptoms (81) and its constituents have been shown to have anti-tumor, antimicrobial, anti-inflammatory, neuroprotective, and cardioprotective effects (100104). One of the active constituents found in Polygonum cuspidatum is a polyphenol called resveratrol.…”
Section: Discussionmentioning
confidence: 99%